A study of how the technological advancements in capturing believable facial emotion in Computer Generated (CG) characters in film has facilitated crossing the uncanny valley - Louis, Clare (My University, 2014)
In recent years, the quest for capturing authentic emotion convincingly in computer generated (CG) characters to assist exceedingly complex narrative expressions in modern cinema has intensified. Conveying human emotion in a digital human-like character is widely accepted to be the most challenging and elusive task for even the most skilled animators. Contemporary filmmakers have increasingly looked to complex digital tools that essentially manipulate the visual design of cinema through innovative techniques to reach levels of undetectable integration of CG characters. In trying to assess how modern cinema is pursuing the realistic integration of CG human-like characters in digital film with frenetic interest despite the risk of box office failure associated with the uncanny valley, this report focuses on the progress of the advances in the technique of facial motion capture. The uncanny valley hypothesis, based on a theory by Sigmund Freud, was coined in 1970 by Japanese robotics professor, Masahiro Mori. Mori suggested that people are increasingly comfortable with robots the more human-like they appear, but only up to a point. At that turning point, when the robot becomes too human-like, it arouses feelings of repulsion. When movement is added to this equation, viewers’ sense of the uncanny is heightened when the movement is deemed to be unreal. Motion capture is the technique of mimicking and capturing realistic movement by utilising technology that enables the process of translating a live actor’s performance into a digital performance. By capturing and transferring the data collected from sensors placed on a body suit or tracked from a high definition video, computer artists are able to drive the movement of a corresponding CG character in a 3-Dimensional (3D) programme. The attention of this study is narrowed to the progress of the techniques developed during a prolific decade for facial motion capture in particular. Regardless of the conflicting discourse surrounding the use of motion capture technology, these phenomenal improvements have allowed filmmakers to overcome that aspect of the uncanny valley associated with detecting realistic movement and facial expression. The progress of facial motion capture is investigated through the lens of selected films released during the period of 2001 to 2012. The two case studies, The Curious Case of Benjamin Button (2008) and Avatar (2009) were chosen for their individual achievement and innovative techniques that introduced new methods of facial capture. Digital images are said to undermine the reality status of cinematic images by challenging the foundation of long held theories of cinematic realist theory. These theories rooted in the indexical basis of photography, have proved to be the origin of contemporary viewers' notion of cinematic realism. However, the relationship between advanced digital effects and modern cinematic realism has created a perceptual complexity that warrants closer scrutiny. In addressing the paradoxical effect that photo-real cinematic realism is having on the basic comprehension of realism in film, the history of the seminal claims made by recognized realist film theorists is briefly examined.
A Research Report submitted in partial fulfilment of the requirement for the Degree of Masters of Arts in Digital Animation at the University of the Witwatersrand (School of Digital Arts) Johannesburg, South Africa
Keywords: Computer animation; Digital art; Animation (Cinematography); Digital images